Case 3668: Conus antidiluvianus Bruguière, 1792 (Mollusca, Gastropoda, Conidae): proposed conservation of prevailing usage of specific name by setting aside the unidentifiable lectotype and replacing it with a neotype. - Janssen, A W; Janssen, R; Tracey, S; Vaessen, L M B; Voort, J van der (Bulletin of Zoological Nomenclature, 2014)
The purpose of this application, under Article 75.5 of the Code, is to conserve prevailing usage of the specific name Conus antidiluvianus Bruguière, 1792 for a Neogene fossil cone shell, widely distributed in Europe. The type locality stated in the original description was an Eocene site in the east of the Paris Basin, France, and three more unlocalised specimens were said to exist in various collections. No specimen resembling the original description has since been found in this area and all of the former syntypes are believed to be lost. The type locality has long been considered to be erroneous and the name Conus antidiluvianus has been almost exclusively applied to the Neogene species by most authors, until relatively recently when this name was applied instead to another Eocene fossil from the central Paris Basin, replacing the widely used name Conus parisiensis Deshayes, 1865. In view of the mismatch between original description and type locality, Conus antidiluvianus Bruguière, 1792 is strictly a nomen dubium. A recent lectotype designation of the (lost) shell originally figured did nothing to clarify the identity of this species, and the present authors have elsewhere published their intention, under Article 75.1, to set aside this lectotype in favour of a specified neotype; however, it might be considered that this would not fully comply with Article 75.3.6 and so a ruling by the Commission is requested in order to maintain stability of nomenclature for this species.
Keywords: Nomenclature; taxonomy; CONIDAE; Conus antidiluvianus; Conus parisiensis; Paris Basin; Italy; fossil cone shells